Muscle Damage Indicators after Land and Aquatic Plyometric Training Programmes - Vlatka Wertheimer; Ljubomir Antekolovic; Branka R. Matkovic (Montenegrin Sports Academy, 2018)
Plyometric training is an important part of athletic conditioning with many significant benefits, including improved motor abilities and performance, but it can also increase the serum indices of muscle damage, collagen breakdown, muscle swelling, and soreness. Due to the physical characteristics of water, plyometric training in water presents less eccentric contraction, facilitates faster transition from the eccentric to concentric phase of a jump and offers greater resistance during concentric contraction with acute lower indices of muscle damage. To advance our understanding of the long-term effects of an eight-week plyometric training programme on land and in water on muscle damage indicators (lactate dehydrogenase (LDH), creatine kinase (CK) and serum urea (SU)), two experimental groups of physically active men (a group on land (EG1) and a group in water (EG2)) were tested before and after the first and the last plyometric training to monitor muscle damage indicators and adaptations. The results showed changes in CK activity after both plyometric trainings for EG1 and only after the first training for EG2. Moreover, after the eight-week programme, significant difference was observed in CK activity in comparison with EG2. There were no observed changes in LDH activity while SU showed greater changes for the group on land. The plyometric training programme in water resulted in smaller levels of muscle damage indicators. Although both experimental groups conducted the same plyometric training with the same jump volume, the eccentric and concentric loads were not the same, so it can be concluded that adaptations in muscle damage processes are faster with smaller eccentric loads.